2018
DOI: 10.1111/jog.13585
|View full text |Cite
|
Sign up to set email alerts
|

Management of pregnancy complicated with intracranial arteriovenous malformation

Abstract: Most of the cases with residual i-AVM lesion and neurological symptoms could deliver vaginally without worsening of symptoms. However, pregnancy with i-AVM can be complicated by rupture of i-AVM. In cases with a residual lesion with indication of treatment and rupture of i-AVM during pregnancy, meticulous care is required during pregnancy and after delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Induction of labor is sometimes preferred in cases wherein the patient is receiving anticoagulation, to allow for better control. Unfractionated heparin and LMWH should be stopped 24h before labor induction and continued 24 h after birth, if no contraindications have developed (Katsuragi et al, 2018).…”
Section: Cerebrovascular Diseasementioning
confidence: 99%
“…Induction of labor is sometimes preferred in cases wherein the patient is receiving anticoagulation, to allow for better control. Unfractionated heparin and LMWH should be stopped 24h before labor induction and continued 24 h after birth, if no contraindications have developed (Katsuragi et al, 2018).…”
Section: Cerebrovascular Diseasementioning
confidence: 99%
“…Multiple observational studies have demonstrated an increased risk of stroke during pregnancy and the postpartum period. However, comparison between studies is limited due to variability in definitions of stroke, categorization of timing (antepartum, peripartum, or postpartum), and study design (use of administrative data (5,6,12,13) versus registry-based (14)(15)(16) or institution-based (17)(18)(19)). While the pregnant state is widely thought of as high risk for stroke due to hypercoagulability and hemodynamic changes, the risk at time of delivery and during the puerperium appears far greater than the antepartum risk (20)(21)(22)(23).…”
Section: Epidemiology and Timing Of Maternal Strokementioning
confidence: 99%
“…Arteriovenous malformations.-Neurosurgical and/or endovascular treatment should be initiated as soon as AVM is identified as a cause of intracranial hemorrhage, due to the risk of rapid clinical deterioration. Cerebral angiogram and embolization with appropriate shielding are considered safe for the fetus (18). Strict blood pressure control during anesthesia is recommended, to avoid expansion of the hematoma while avoiding placental hypoperfusion (23).…”
Section: Management Of Hemorrhagic Stroke In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Dear Editor, We read the article by Shinji Katsuragi et al 1 with great interest and congratulate the authors on their review of cases and presentation of the data regarding the management of pregnancies complicated by intracranial arteriovenous malformation (AVM). However, we would like to add a few points.…”
mentioning
confidence: 99%